Method for recycling phosphorus and nickel resources in chemical nickel-plating wastewater and synthesizing high-purity iron phosphate through paired electrolysis method

The phosphorus and nickel resources in the electroless nickel plating waste liquid are recovered through pairwise electrolysis, and lithium iron phosphate is prepared in combination with solid phase method, which solves the problems of long processing flow and low resource degree in the existing technology, and achieves low cost and high quality The preparation of lithium iron phosphate and the improvement of lithium-ion battery performance.

CN119287399AActive Publication Date: 2025-01-10ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411473822.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing electroless nickel plating waste liquid treatment technology has the problems of long processing flow, large amount of chemical reagents, low degree of resource utilization, and low added value, and it is difficult to achieve low-cost and high-quality lithium iron phosphate preparation technology.

Method used

Paired electrolysis method is used to recover phosphorus and nickel resources in electroless nickel plating waste liquid, through double chamber separator electrolytic cell and anion exchange membrane, the anode recovers phosphorus resources to synthesize high-purity iron phosphate, cathode electrodeposited nickel resources, and prepared in combination with solid phase method Lithium iron phosphate positive electrode material.

Benefits of technology

It realizes the resource utilization of electroless nickel plating waste liquid, reduces production costs, improves the purity of lithium iron phosphate and battery performance, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287399A_ABST
    Figure CN119287399A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of industrial wastewater recycling and lithium ion battery positive electrode material preparation, and relates to a method for recycling phosphorus and nickel resources in chemical nickel plating wastewater and synthesizing high-purity iron phosphate through a paired electrolysis method. The method comprises the steps that a double-chamber diaphragm electrolytic cell is adopted, a diaphragm is an anion exchange membrane, an anode is iron, a cathode is at least one of a metal electrode, an alloy electrode and a graphite electrode, an anolyte is a solution containing sulfate radicals, a catholyte is chemical nickel-plating wastewater, a paired electrolysis method is adopted, phosphorus resources are recycled from the anode, and high-purity iron phosphate is synthesized. And nickel resources are recovered through cathode electrodeposition of nickel. According to the method, phosphorus and nickel are recycled through an electro-deposition method, and the current efficiency is greatly improved; the method is high in recovery rate, low in cost and simple in process, industrial large-scale production can be realized, and the recovered iron phosphate has very high purity and can be used as a precursor raw material for synthesizing lithium iron phosphate serving as a positive electrode material of a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial wastewater recycling and lithium ion battery positive electrode material preparation, and relates to a technology for recovering phosphorus and nickel resources from chemical nickel plating waste liquid and synthesizing high-purity lithium iron phosphate. Background Art

[0002] Chemical nickel plating is a surface treatment technology that does not require an external current. It has the advantages of corrosion resistance, all-plating ability, high hardness, wear resistance, high welding performance, certain electromagnetic shielding ability, and no restrictions on the size and shape of parts. Chemical nickel plating is widely used in many fields such as electronics, aviation, automobiles, and machinery. With the continuous expansion of the application scope and production scale of chemical nickel plating technology, the resulting environmental problems are becoming more and more serious. The industrial chemical nickel plating solution becomes ineffective after 8-10 uses and becomes chemical nickel plating waste liquid. Its main components are heavy metal nickel and a large amount of phosphate (hypophosphite, phosphite, orthophosphate and pyrophosphate, etc.). The former has carcinogenic, teratogenic and mutagenic risks to the human body, and the latter is one of the pollutants that cause eutrophication of the water environment. Chemical nickel plating waste liquid treatment technologies include oxidation precipitation, ion exchange and electrodialysis, etc., which mainly focus on the removal of phosphorus or nickel. There are problems such as long treatment process, large amount of chemical reagents, low product resource utilization, and low added value. At present, there is little research on the use of chemical nickel plating waste liquid for the preparation of lithium-ion battery positive electrodes.

[0003] In recent years, the sales of new energy vehicles in my country have grown rapidly. According to the latest data from the China Association of Automobile Manufacturers, in 2023, the sales volume of China's automobile market will reach 30.094 million vehicles, of which the sales volume of new energy vehicles will reach 9.495 million vehicles, accounting for 31.6%. Power batteries account for nearly 40% of the cost of new energy vehicles, of which the cost of positive electrode materials in power batteries reaches 51%. The positive electrode materials of new energy vehicle power batteries mainly include nickel-cobalt-manganese, nickel-cobalt-aluminum ternary positive electrode materials, lithium iron phosphate (LiFePO4, referred to as LFP) positive electrode materials, lithium cobalt oxide positive electrode materials and lithium manganese oxide positive electrode materials. Among them, lithium-ion batteries with LFP as positive electrode materials will surpass ternary material batteries in 2021 and occupy a dominant position in new energy vehicle power batteries due to their advantages such as high energy density, low cost, rich resources and higher safety. In addition, LFP is also a key material for the transformation of energy storage batteries from commercialization to scale. Broadening the source of LFP raw materials and increasing the scale of LFP production are urgent needs for the development of new energy vehicles and energy storage industries.

[0004] The main methods for preparing lithium iron phosphate in industry are solid phase method and hydrothermal method, both of which use iron phosphate as raw material. These two methods are simple in process, high in raw material utilization, good in repeatability, and high in activity of positive electrode materials. The production technology is becoming more and more mature and is the mainstream process for preparing lithium iron phosphate. The performance and cost of lithium iron phosphate prepared by this technology mainly depend on the purity, morphology and cost of the iron phosphate precursor. With the vigorous development of the new energy industry, the profits of lithium iron phosphate have been continuously compressed, and new technologies for preparing low-cost and high-quality iron phosphate are in demand in the market. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of phosphorus and nickel pollution and waste in the existing chemical nickel plating wastewater, as well as the technical problems of low-cost and high-quality lithium iron phosphate preparation. The present invention provides a method for recovering phosphorus and nickel resources in chemical nickel plating wastewater and synthesizing high-purity iron phosphate by a paired electrolysis method. Compared with the existing preparation method, this method has the following outstanding advantages: (1) chemical nickel plating wastewater is recycled; (2) a new method for synthesizing iron phosphate, a precursor of lithium iron phosphate, is provided; (3) the method has a lower production cost; (4) the technology is easy to industrialize. The iron phosphate obtained by the method of the present invention is used as a precursor to prepare lithium iron phosphate positive electrode material by a solid phase method, and assembled into a lithium-ion battery to obtain a battery performance consistent with commercial lithium iron phosphate.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0007] A method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate, the method comprising: using a double-chamber diaphragm electrolytic cell, wherein: the diaphragm is an anion exchange membrane, the anode is iron, the cathode is at least one of a metal, an alloy and a graphite electrode, the anolyte is a solution containing sulfate, the cathode electrolyte is chemical nickel plating wastewater, and the paired electrolysis method is used to recover phosphorus resources at the anode to synthesize high-purity ferric phosphate, and to recover nickel resources by electrodepositing nickel at the cathode.

[0008] Preferably, the cathode is at least one of metals such as iron, nickel, stainless steel, titanium, and alloys such as lead alloys, which can further improve the recovery rate of nickel and phosphorus.

[0009] Preferably, the membrane is a quaternary ammonium anion exchange membrane.

[0010] Preferably, the sulfate-containing solution includes at least one of a sulfate solution and a dilute sulfuric acid solution; more preferably, the sulfate includes at least one of ammonium sulfate, lithium sulfate, and sodium sulfate; the ratio of the sulfate concentration (g / L) in the sulfate-containing solution to the sulfate concentration (g / L) in the chemical nickel plating wastewater is 0.5-4:1, more preferably 1-4:1.

[0011] Preferably, the paired electrolysis is performed by constant current electrolysis, the method being: controlling the anode current density to be 150-450A / m 2 , cathode current density is 50-300A / m 2 The ratio of the anode and cathode current density is regulated by the anode and cathode area ratio method, the area ratio is 1:1-5, and the constant current paired electrolysis recovers most of the nickel, and the recovery rate is not less than 80%. More preferably, the anode current density is 300-450A / m 2 More preferably, the constant current electrolysis time is 3-5h, and the constant current electrolysis is performed until the phosphorus recovery rate reaches about 55%, or the color of the chemical nickel plating waste liquid in the cathode area is close to colorless (generally in 3-5h), so that most of the nickel and part of the phosphorus can be recovered. The constant current electrolysis time can be longer, but it will cause higher energy consumption.

[0012] Preferably, the paired electrolysis adopts variable current electrolysis, and the variable current electrolysis includes two constant current electrolysis processes, and the method is: the aforementioned constant current electrolysis is used as a first constant current electrolysis, and when the phosphorus recovery rate is greater than 55%, or the color of the chemical nickel plating waste liquid in the cathode area is close to colorless, a small current constant current electrolysis is used as a second constant current electrolysis; the small current of the second constant current electrolysis is less than the current of the first constant current electrolysis; more preferably, the cathode current density of the second constant current electrolysis is controlled to be 30-150A / m 2 Recover nickel, anode current density is 150A / m 2 , constant current electrolysis recovers most of the phosphorus, with a recovery rate of not less than 60%; the more preferred small current constant current electrolysis time is about 2 hours. Using variable current electrolysis can further improve the recovery rate of phosphorus and reduce energy consumption.

[0013] Preferably, the method for treating the electrolysis product in the anode region is: taking out the turbid liquid in the anode region, filtering it, washing it with water until the pH is around 7.0, filtering the product and drying it to obtain high-purity hydrated iron phosphate, preferably at a drying temperature of 80° C. More preferably, the hydrated iron phosphate is calcined to obtain iron phosphate, and the calcination temperature is preferably 650° C.

[0014] Preferably, the method for treating the electrolysis product in the cathode region is: washing the nickel glass deposited on the cathode electrode with water until the pH is around 7.0, filtering the product and drying it to obtain nickel, and preferably the drying temperature is 80°C.

[0015] Furthermore, the hydrated iron phosphate obtained by electrolysis is high-purity hydrated iron phosphate, and high-purity iron phosphate is obtained after calcination; under preferred electrolysis conditions, the iron-phosphorus ratio of the product is in the range of 0.96-1.02, which can meet the battery-grade iron phosphate standard (Iron Phosphate for Batteries "HG / T 4701-2021").

[0016] Preferably, the hydrated iron phosphate or calcined iron phosphate obtained from the anode region is used as a precursor of lithium iron phosphate, a positive electrode material of a lithium ion battery, and lithium iron phosphate@carbon is synthesized by a solid phase method, and a lithium ion battery is assembled to test the performance of the battery. The lithium iron phosphate positive electrode material synthesized from the iron phosphate recovered by the present invention meets the quality standards of commercial-grade lithium ion battery positive electrode material raw materials.

[0017] Furthermore, the lithium iron phosphate cathode material synthesized from the prepared iron phosphate has good purity. The prepared lithium iron phosphate half-cell has good performance. The first discharge capacity at 0.1C is 158.1mAh / g, and the first coulomb efficiency is 89.98%. After 60 cycles at 0.1C, the discharge capacity retention rate is 98.67%, and after 500 cycles at 1C, the discharge capacity retention rate is 88.95%.

[0018] Compared with the existing chemical method for recovering waste phosphorus and nickel resources, the beneficial effects of the technical solution described in the present invention are embodied in the following aspects: (1) The present invention adopts a paired electrodeposition method for recovering phosphorus and nickel, which greatly improves the current efficiency and has a high recovery rate; (2) The present invention adopts a method of using a single anion diaphragm, which is simple in process and can obtain high-purity iron phosphate; (3) A new type of anolyte is developed, which greatly improves the selective permeation of phosphite anions through the anion membrane by regulating the ratio of sulfate in the anode and cathode regions, thereby significantly improving the current efficiency and recovery efficiency; (4) It avoids the consumption of a large amount of hydrogen peroxide in the chemical method; (5) The method described in the present invention is low in cost, simple to operate, and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a process flow chart of the present invention;

[0020] Figure 2 It is a structural diagram of the electrolysis device of the present invention;

[0021] Among them, 1-anode, 2-anion exchange membrane, 3-cathode, 4-anode chamber, 5-cathode chamber

[0022] Figure 3 This is a SEM image of the iron phosphate synthesized in Example 1;

[0023] Figure 4 This is the XRD pattern of the iron phosphate synthesized in Example 1;

[0024] Figure 5 This is the XRD pattern of lithium iron phosphate synthesized in Example 1;

[0025] Figure 6 This is a comparison diagram of the first charge and discharge curves of the lithium iron phosphate half-cell assembled by Example 1 and the chemical precipitation method;

[0026] Figure 7This is a comparison chart of the cyclic discharge performance at 0.1C of the lithium iron phosphate half-cell assembled by Example 1 and the chemical precipitation method.

[0027] Figure 8 This is a comparison chart of the cyclic discharge performance at 1C of the lithium iron phosphate half-cell assembled by Example 1 and the chemical precipitation method. DETAILED DESCRIPTION

[0028] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] The experimental methods and conditions used in the following examples are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the examples, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product with the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.

[0030] Embodiment 1:

[0031] The process flow chart of this experiment is as follows Figure 1 .

[0032] S1. Electrolyte pretreatment. Take the chemical nickel plating waste liquid of a certain enterprise, the pH is about 4. The main components of the waste liquid are obtained by ICP test method as shown in Table 1.

[0033] Table 1 Main components of chemical nickel plating wastewater

[0034]

[0035] Filter the chemical nickel plating waste liquid with a filter device. Dilute the above waste liquid (phosphorus content 60g / L, nickel content 6g / L, sulfur content 30g / L) 5 times (phosphorus content 12g / L, nickel content 1.2g / L, sulfur content 6g / L) as the cathode chamber electrolyte; configure a (NH4)2SO4 solution with a concentration of 0.12mol / L as the anode electrolyte (sulfate concentration is about 12g / L, and the ratio of sulfate content in the anode electrolyte and the cathode electrolyte is about 2:1).

[0036] S2, electrolysis experiment. Figure 2 As shown, using Figure 2 The double-chamber electrolytic cell has an anion exchange membrane (2) as a separator in the middle. The cathode electrolyte is injected into the cathode chamber (5), and the anolyte is injected into the anode chamber (4). A DT4C type anode iron plate (1) and a 304 type cathode stainless steel plate (2) are placed in the two chambers respectively. 铁板 :S 不锈钢板 =1:3.

[0037] One stage of constant current electrolysis: adjust the anode current density to 300A / m 2 , cathode current density is 100A / m 2 , the electrolyte temperature is room temperature (room temperature is 15-40°C, preferably 25°C), the temperature rises naturally during the electrolysis process, and an appropriate amount of water is added to keep the electrolyte volume of the cathode and anode regions substantially unchanged. During electrolysis, anions such as hypophosphite and sulfate in the chemical nickel plating waste liquid enter the anode chamber through the anion membrane under the action of the electric field to form a phosphorus concentrate, while the hypophosphite ions react with the ferrous ions dissolved from the iron anode under the participation of oxygen to form iron phosphate, and the anode region solution is a light yellow suspension. Nickel ions are reduced to nickel at the cathode and deposited on a stainless steel plate. When the color of the cathode wastewater solution is close to colorless, the phosphorus-nickel content in the cathode wastewater before and after the reaction is determined by ICP, and the paired electrodeposition cathode nickel recovery rate is 96%, the anode phosphorus recovery rate is 56%, the cathode current efficiency is 30%, and the anode current efficiency is 84%.

[0038] Among them, the nickel and phosphorus recovery rates and current efficiency are calculated as shown in the following formula:

[0039]

[0040] C0——Ni and P concentrations on the cathode side measured by ICP before the reaction;

[0041] C1——Ni and P concentrations on the cathode side measured by ICP after the reaction;

[0042] V0——the volume of cathode electrolyte before reaction;

[0043] V1——the volume of cathode electrolyte after reaction.

[0044]

[0045] Second stage constant current electrolysis: When the color of the wastewater solution in the cathode area is close to colorless, most of the nickel has been recovered. At the same time, as the phosphorus content in the solution decreases, the rate of ferric phosphate synthesis in the anode area and the anode current efficiency decrease. At this time, the anode current density is adjusted to 150A / m 2 , cathode current density is 50A / m 2, S 铁板 :S 不锈钢板 =1:3, the electrolyte temperature is room temperature, the temperature rises naturally during the electrolysis process, and an appropriate amount of water is added to keep the electrolyte volume in the cathode and anode areas basically unchanged. Use a small current to continue constant current electrolysis to reduce energy consumption and increase product yield. The electrolysis time is about 2h, the cathode current efficiency of the second stage electrolysis is 0, and the anode current efficiency is 42%. After one or two stages of constant current electrolysis, the total nickel recovery rate is 98%, and the total phosphorus recovery rate is 70%.

[0046] S3, product treatment. The suspension was taken out from the anode chamber, filtered, washed with water, and dried at 80°C to obtain nano-scale hydrated iron phosphate ( Figure 3 The hydrated iron phosphate was calcined in air at 650°C to obtain anhydrous iron phosphate ( Figure 4 The XRD pattern of the iron phosphate synthesized in Example 1); the deposit on the cathode stainless steel plate was scraped off, washed and dried to obtain nickel metal.

[0047] S4, synthesis of lithium iron phosphate positive electrode material. Lithium hydroxide and the above-mentioned hydrated iron phosphate or anhydrous iron phosphate were mixed in a ratio of 1.02:1, and an appropriate amount of glucose was added as a carbon source. After ball milling for 12 hours, the temperature was raised to 380°C at a rate of 10°C / min under an inert atmosphere and kept for 1 hour, and then the temperature was raised to 650°C at a rate of 10°C / min and kept for 6 hours to obtain lithium iron phosphate ( Figure 5 ). Add the above-mentioned lithium iron phosphate, PVDF and SP in a ratio of 8:1:1 to NMP solvent, stir and mix to obtain positive electrode slurry, and coat the positive electrode slurry on the aluminum sheet with a coating amount of 1.1 mg / cm 2 The obtained product was dried in an oven at 60°C for 2 h, and finally kept in a vacuum oven at 110°C for 12 h to obtain a lithium iron phosphate positive electrode sheet.

[0048] S5. Battery assembly. Assemble the half-cell in an argon atmosphere glove box. The assembly order is: battery positive electrode shell, positive electrode sheet, battery separator, negative electrode lithium sheet, gasket, spring, battery negative electrode shell.

[0049] S6. Battery test. The electrochemical performance of the battery was tested using a Xinwei tester. The first discharge capacity at 0.1C was 158.1mAh / g, and the first coulombic efficiency was 89.98% ( Figure 6 After 60 cycles at 0.1C, the discharge capacity retention rate is 98.67% ( Figure 7 ), after 500 cycles at 1C, the discharge capacity retention rate is 88.95% ( Figure 8 ). It has the same battery performance as commercial lithium iron phosphate.

[0050] Embodiment 2-6

[0051] The same method as in Example 1 was used, except that the cathode in S2 was replaced with iron (DT4C), nickel (N6), and titanium (TA1) and a graphite electrode (SHCM-7) and a lead alloy (PbSb2), and one-stage and two-stage electrolysis was used to recover nickel and iron phosphate, and prepare lithium iron phosphate positive electrode materials. The experimental results are shown in Table 2.

[0052] Table 2 Experimental results of different cathode materials

[0053]

[0054] The results in Table 2 show that different cathode materials have a significant impact on the recovery rate of phosphorus nickel, which may be due to the fact that the conductivity and hydrogen evolution potential of different electrode materials affect the electrochemical reaction process.

[0055] Embodiment 7-9

[0056] The same method as in Example 1 was used, except that the anode electrolyte in S1 was replaced with lithium sulfate, sodium sulfate and dilute sulfuric acid solution, respectively, and nickel and iron phosphate were recovered by one-stage and two-stage electrolysis to prepare lithium iron phosphate positive electrode material. The experimental results are shown in Table 3.

[0057] Table 3 Experimental results of different anolytes

[0058]

[0059] The results in Table 3 show that the type of sulfate in the anolyte has little effect on the recovery of phosphorus and nickel.

[0060] Examples 10-12

[0061] The same method as in Example 1, the sulfate concentration (g / L) in the first-stage anolyte solution in S1 and the sulfate concentration (g / L) in the cathode region were changed to 0.5:1, 1:1, 4:1, respectively. The current efficiency and recovery rate experimental results of the first-stage electrolysis and the second-stage electrolysis are shown in Table 4.

[0062] Table 4 Experimental results of different anode and cathode electrolyte sulfate concentration ratios

[0063]

[0064] The results in Table 4 show that the concentration ratio of sulfate in different anolytes and catholytes has a significant effect on phosphorus recovery, but has little effect on nickel recovery. This may be because when the sulfate concentration in the anode region is low, due to the influence of ion concentration difference and electrical driving force, the sulfate ions in the cathode region preferentially pass through the anion membrane compared with the hypophosphite ions, generating impurities such as iron sulfate (soluble in water), increasing the amount of precipitate washing water, and reducing the yield and efficiency of synthetic iron phosphate. When the sulfate concentration in the anode region is high and reaches a certain proportion, this effect is weakened. When the sulfate concentration in the anode region is too high, the excessive ion concentration may reduce the driving force for ion migration.

[0065] Examples 13-15

[0066] The same method as in Example 1, in S1, the cathode electrolyte was treated by undilution, dilution 2 times with deionized water, and dilution 10 times with deionized water (the purpose is to adjust the phosphorus nickel concentration in the waste liquid), and the experimental results of the current efficiency and recovery rate of the first-stage electrolysis and the second-stage electrolysis are shown in Table 5.

[0067] Table 5 Experimental results of wastewater treatment at different dilution multiples

[0068]

[0069]

[0070] The results in Table 5 show that within a certain range, as the dilution ratio increases, the recovery rate of phosphorus and nickel increases. This may be because too high ion concentration may cause blockage of anion membrane pores and reduce conductivity. However, too high a dilution ratio will increase the amount of water used and reduce the yield of iron phosphate.

[0071] Examples 16-17

[0072] The same method as in Example 1, in a constant current electrolysis of S2, the anode current density was adjusted to 150 and 450 A / m respectively. 2 In the two-stage constant current electrolysis, the anode current density is maintained at 150A / m 2 The experimental results of the current efficiency and recovery rate of the first-stage electrolysis and the second-stage electrolysis are shown in Table 6.

[0073] Table 6 Experimental results of a constant current electrolysis at different current densities

[0074]

[0075] The results in Table 6 show that the higher the current density during a constant current electrolysis, the higher the phosphorus nickel recovery rate, but the current efficiency decreases and the energy consumption increases.

[0076] Examples 18-19

[0077] The method of Example 1 is the same as that of Example 1. In S2, by controlling the anode and cathode area ratio (S 铁板 :S 不锈钢板 ) method, the cathode and anode current density ratios were adjusted to 1:1 and 1:5 respectively. The anode current density in one section of constant current electrolysis was constant at 300A / m 2 The anode current density in the two-stage constant current electrolysis is constant at 150A / m 2 The experimental results of the current efficiency and recovery rate of the first-stage electrolysis and the second-stage electrolysis are shown in Table 7.

[0078] Table 7 Experimental results of different anode and cathode area ratios

[0079]

[0080] Table 7, the results show that after adjusting the anode and cathode area ratio, the phosphorus and nickel recovery rate does not change significantly, but there is an impact on the phosphorus and nickel recovery current efficiency.

[0081] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solutions described in the claims.

Claims

1. A method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate, characterized in that: The method comprises: using a double-chamber diaphragm electrolytic cell, wherein: the diaphragm is an anion exchange membrane, the anode is iron, the cathode is at least one of a metal, an alloy and a graphite electrode, the anode electrolyte is a solution containing sulfate, the cathode electrolyte is chemical nickel plating wastewater, and a paired electrolysis method is adopted to recover phosphorus resources at the anode and nickel resources at the cathode.

2. According to claim 1, a method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate, characterized in that: The cathode is at least one of iron, nickel, stainless steel, titanium and lead alloy.

3. The method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 1, characterized in that: The diaphragm is a quaternary ammonium anion exchange membrane.

4. The method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 1, characterized in that: The sulfate-containing solution comprises at least one of a sulfate solution and a dilute sulfuric acid solution; the ratio of the sulfate concentration (g / L) in the sulfate-containing solution to the sulfate concentration (g / L) in the chemical nickel plating wastewater is 0.5-4:

1.

5. A method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 4, characterized in that: The ratio of the sulfate concentration (g / L) in the sulfate-containing solution to the sulfate concentration (g / L) in the chemical nickel plating wastewater is 1-4:

1.

6. The method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 1, characterized in that: The paired electrolysis is performed by constant current electrolysis, and the method is: controlling the anode current density to 150-450A / m 2 , cathode current density is 50-300A / m 2 The ratio of anode and cathode current density is regulated by the anode and cathode area ratio method, and the area ratio is 1:1-5.

7. A method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 6, characterized in that: Anode current density is 300-450A / m 2 .

8. A method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 6 or 7, characterized in that: The paired electrolysis adopts variable current electrolysis, and the variable current electrolysis includes two constant current electrolysis processes, including: using the constant current electrolysis of claim 6 or 7 as one constant current electrolysis; when the phosphorus recovery rate is greater than 55%, or the color of the chemical nickel plating waste liquid in the cathode area is close to colorless, switching to small current constant current electrolysis as the second constant current electrolysis; the current of the second constant current electrolysis is less than the current of the first constant current electrolysis.

9. A method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 8, characterized in that: Two-stage constant current electrolysis controls the cathode current density to 30-150A / m 2 , the anode current density is 150A / m 2 .

10. The method for recovering phosphorus and nickel resources from chemical nickel plating wastewater by paired electrolysis and synthesizing high-purity ferric phosphate according to claim 1, characterized in that: The method for treating the electrolysis product in the anode region is as follows: taking out the turbid liquid in the anode region, filtering it, washing it with water, and drying the filtered product to obtain hydrated iron phosphate; The method for treating the electrolysis product in the cathode region is as follows: washing the nickel glass deposited on the cathode electrode with water, filtering the product and drying it to obtain nickel.

Citation Information

Patent Citations

  • Treatment process for chemical nickel plating waste liquid in circuit board industry

    CN104176852A

  • Method of purifying nickel from chemical nickel-plating waste liquid and nickel purification device

    CN104532293A

  • Chemical nickel plating aging liquid reduction regeneration method

    CN113026003A

  • Method and system for recovering phosphorus from acidic chemical nickel-plating waste liquid

    CN113716659A

  • Recycling method of ferrophosphorus slag

    CN117545714A

Cited By

  • Electrodialysis phosphorus extraction method based on biomass porous carbon electrode

    CN120247183A

  • A method for treating waste lithium iron phosphate by diaphragm electrolysis and cooperatively synthesizing lithium iron phosphate precursor

    CN122707143A